Stakeholder-Oriented Firms Have Feelings and Moral Standing Too - Quintelier, Katinka J. P. (Frontiers in Psychology, 2022)
A central claim in stakeholder theory is that, if we see stakeholders as human beings, we will attribute higher moral standing or show more moral consideration to stakeholders. But would the same hold for firms? In this paper, I apply the concepts of humanization and moral standing to firms, and I predict that (1) individuals attribute higher moral standing to stakeholder-oriented than to profit-oriented firms, because (2) individuals attribute more experience (such as feelings) to stakeholder-oriented than to profit-oriented firms. Five experiments support these predictions across different operationalizations of stakeholder and profit orientations. The analyses show that moral standing attributions are not fully explained by attributions of agency (such as thinking) to firms, or by attributions of experience or agency to human stakeholders (instead of firms). By unearthing the importance of experience attributions for moral standing attributions to firms, this work provides novel insights in ongoing legal, philosophical and public debates related to firms’ moral standing. The findings also bring the debate about firms’ moral standing to the heart of stakeholder theory, and lead to new normative and descriptive research questions about the interests of firms and their stakeholders.